The impact of extralegal characteristics on recognizance release among misdemeanants. Issue 2 (2nd April 2016) - Ortiz, Mia
ABSTRACT: The purpose of this study is to direct attention to pretrial release decisions on low-level offenders and to assess whether certain characteristics influence the pretrial release outcome. Bivariate correlations and stepwise logistic regression were used to analyze a 2004 primary data set of misdemeanants considered for release on recognizance in a California court ( N = 539). The results showed that Hispanic defendants were more likely to be granted this condition of release. This finding is particularly noteworthy because it is in contrast with prior studies that found that defendants of color were less likely to be granted less restrictive release conditions. Furthermore, such a result may lead to imply that Hispanic Americans may be less stigmatized and more integrated in society.